PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, & PROFITABILITAS TERHADAP HASIL PEMERINGKATAN KOPERASI OLEH LIPK LP2UKM DI KALSEL TAHUN 2021 - Diani Koesasih, Myalda; Limarjani, Sustinah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
The purposes of this study are to find out and analyze the effect of liquidity, solvency and profitability ratios on the cooperative ranking results by LIPK LP2UKM in South Kalimantan in 2021. The independent variables used in this study are liquidity ratios, solvency ratios and profitability ratios. Meanwhile, the dependent variable used in this study is the cooperative ranking results. The population used in this this study is all cooperatives ranked by LIPK LP2UKM in 2021 with a total amount of 50 cooperatives. The sample selection in this study used a purposive sampling method with a total amount of 47 cooperatives. This research is a quantitative descriptive study using secondary data in the form of Cooperative Ranking Reports for 2021 and Cooperative Financial Reports. Data are processed using multiple linear regression analysis through SPSS version 26.0. The results of this study prove that the liquidity ratio has an effect on cooperative ranking results, the solvency ratio has an effect on cooperative ranking results, and the profitability ratio has no effect on cooperative ranking results.